Does Monetary Policy React to Asset Prices? Some International Evidence - Francesco Furlanetto (Norges Bank, 2008)
This paper attempts to measure the reaction of monetary policy to the stock market. We apply the procedure of Rigobon and Sack (2003) to identify and estimate a VAR in the presence of heteroskedasticity. This procedure fully takes into account the endogeneity of interest rates and stock returns that is ignored in the traditional VAR literature. We find a positive and significant reaction in the US and the UK. However, since the end of the 1990s, in a period of large stock market fluctuations, this reaction declines in the US and disappears in the UK. In Japan and the EU, we do not find any reaction. We provide evidence that the lower response to stock prices in the last part of the sample in the US is compensated by a higher response to real estate prices.
hdl:11250/2497778
Keywords: E44; E52; E58; 330; VAR; monetary policy; stock market; identification; heteroskedasticity